[latex]1. \begin{array}{ccc}9\\56\end{array} - (\begin{array}{ccc}7\\15\end{array} - \begin{array}{ccc}5\\12\end{array}) (\begin{array}{ccc}3\\14\end{array} + \begin{array}{ccc}1\\2\end{array})=... 2.(\begin{array}{ccc}2\\3\end...

[latex]1. \begin{array}{ccc}9\\56\end{array} - (\begin{array}{ccc}7\\15\end{array} - \begin{array}{ccc}5\\12\end{array}) (\begin{array}{ccc}3\\14\end{array} + \begin{array}{ccc}1\\2\end{array})=...  2.(\begin{array}{ccc}2\\3\end{array} + \begin{array}{ccc}7\\8\end{array} - \begin{array}{ccc}5\\6\end{array}) (1 - \begin{array}{ccc}5\\17\end{array})=...[/latex]
Гость
Ответ(ы) на вопрос:
Гость
9/56-97/15-5/12)*(3/14+1/2)=9/56-(28/60-25/60)*(3/14+7/14)= =9/56-(1/2*5/7)=9/56-1/28=9/56-2/56=7/56=1/8 (2/3+7/8-5/6)*(1-5/17)=(16/24+21/24-20/24)*(17/17-5/17)= =17/24*12/17=1/2
Не нашли ответ?
Ответить на вопрос
Похожие вопросы